2016
DOI: 10.1371/journal.pone.0166869
|View full text |Cite
|
Sign up to set email alerts
|

High Vitamin D Consumption Is Inversely Associated with Cardiovascular Disease Risk in an Urban Mexican Population

Abstract: BackgroundVitamin D deficiency is a major global public health problem. Recent epidemiological studies have assessed the relationship between vitamin D and multiple outcomes, including cardiovascular disease. However, this evidence is limited and inconclusive. Our purpose in this study was to evaluate the association between dietary vitamin D intake and cardiovascular disease risk in adult Mexican population.MethodsWe conducted a cross-sectional analysis with the baseline data from 6294 men and women aged 20–8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Several studies have shown that subjects with the adequate serum 25(OH)D concentration and high vitamin D intake have a more favorable lipid profile than those with vitamin D deficiency [3,22,41,[43][44][45][46]. The most often observed changes include a vitamin D-induced decrease in triglycerides and an increase in HDL-C.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that subjects with the adequate serum 25(OH)D concentration and high vitamin D intake have a more favorable lipid profile than those with vitamin D deficiency [3,22,41,[43][44][45][46]. The most often observed changes include a vitamin D-induced decrease in triglycerides and an increase in HDL-C.…”
Section: Discussionmentioning
confidence: 99%
“…Its few food sources include: fatty fish, eggs, fortified beverages and dairy products [1]. This prohormone has various functions in the human body, including bone mineralization, modulation of cell growth, regulation of calcium and phosphorus absorption from the gut, adjustment of the immunological system, and reduction of inflammation [2][3][4]. Therefore, it not only plays an important role in the pathogenesis of skeletal disorders but its impact on the risk of metabolic abnormalities also deserves special attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent cohort study in Mexico documented an inverse association between VD intake and cardiovascular risk factors among adults; however, the sample was not nationally representative and 25-OH-D levels were not measured [23]. In addition, most international reports on the relationship between VDD and cardiovascular risks have not addressed several cardiovascular risks together, and few research efforts have focused on young and/or non-pregnant women [6].…”
Section: Introductionmentioning
confidence: 99%